What About Men? The Marginalization of Men Who Engage in Domestic Violence - Kuskoff, Ella (Journal of interpersonal violence, 2022)
In an international policy context that is increasingly recognizing the gendered nature of domestic violence, governments are becoming more attuned to the importance of improving policy responses for women who have domestic violence enacted against them. This has not, in general, been accompanied by a similar focus on improving policy responses to men who engage in domestic violence, despite a burgeoning body of scholarship suggesting that improved responses to such men are required to more effectively prevent domestic violence from occurring. Importantly, current scholarship also highlights the significant and complex tensions that may arise when policy informed by gendered understandings of domestic violence increases its focus on the men who enact it. Drawing on a critical discourse analysis methodology, we analyze how these tensions are negotiated in domestic violence policy in the Australian state of Queensland. Findings from this analysis demonstrate that the way government policy discursively constructs men who engage in domestic violence has important implications for how such policy targets and engages with members of this group. The article demonstrates that when such men are constructed as outsiders to the community, they may be viewed as undeserving of inclusion and support. This can result in governments failing to prioritize interventions targeted at men who engage in domestic violence, and prevent the active inclusion of such men in the development of policy and interventions. These findings provide important lessons for international governments seeking to implement or strengthen policy responses to end domestic violence against women.